XXI Century – The Century of Informatization: Traditional and Innovative Teaching of Foreign Languages - Abdullaevna, Ismatullaeva Zulfira (International Journal on Integrated Education, 2023)
Russian language teaching methods in modern education, the recommendation of the use of innovative teaching technologies (new forms and methods of teaching, a new approach to the learning process), which improve the quality of teaching Russian as a foreign language, form and develop their communicative culture, teach practical mastery of a foreign language, are presented in this article.